Interventions to support family caregivers of people with advanced dementia at the end of life in nursing homes: A mixed-methods systematic review. (February 2022) - Gonella, Silvia; Mitchell, Gary; Bavelaar, Laura; Conti, Alessio; Vanalli, Mariangela; Basso, Ines; Cornally, Nicola
Background: Most people with dementia transition into nursing homes as their disease progresses. Their family caregivers often continue to be involved in their relative's care and experience high level of strain at the end of life. Aim: To gather and synthesize information on interventions to support family caregivers of people with advanced dementia at the end of life in nursing homes and provide a set of recommendations for practice. Design: Mixed-Methods Systematic Review (PROSPERO no. CRD42020217854) with convergent integrated approach. Data sources: Five electronic databases were searched from inception in November 2020. Published qualitative, quantitative, and mixed-method studies of interventions to support family caregivers of people with advanced dementia at the end of life in nursing home were included. No language or temporal limits were applied. Results: In all, 11 studies met the inclusion criteria. Data synthesis resulted in three integrated findings: (i) healthcare professionals should engage family caregivers in ongoing dialog and provide adequate time and space for sensitive discussions; (ii) end-of-life discussions should be face-to-face and supported by written information whose timing of supply may vary according to family caregivers' preferences and the organizational policies and cultural context; and (iii) family caregivers should be provided structured psychoeducational programs tailored to their specific needs and/or regular family meetings about dementia care at the end of life. Conclusion: The findings provide useful information on which interventions may benefit family caregivers of people with advanced dementia at the end of life and where, when, and how they should be provided.